Rock engineering design - Feng, Xia-Ting.; Hudson, J. A. (John A.), 1940- (Leiden, The Netherlands : CRC Press/Balkema, 2011)
"Given the recent advances in site investigation techniques, computing, access to information and monitoring, plus the current emphasis on safety, accountability and sustainability, the intention of this book is to introduce an up-to-date methodology for the design of all types of rock engineering projects, whether surface or underground. Guidance is provided on the nature of the modeling to support design and the information required for design; also included is a procedure for technical auditing the modeling and design together with the related protocol sheets. This modern approach to Rock Engineering Design includes a CD-ROM with protocol sheets. Written by two eminent authors, clearly structured and with many illustrations, this volume is intended for consulting engineers, contractors, researchers, lecturers and students work on rock engineering projects"--
"The subject of rock engineering design, supported by the discipline of rock mechanics, relates to construction on and in rock masses of projects such as slopes, dams, hydroelectric schemes, mines and repositories for radioactive waste disposal"--
Includes bibliographical references and index.
Keywords: Rock mechanics; Engineering geology